TRANSFORMASI TATA KELOLA KPBU DALAM DINAMIKA PEMBANGUNAN WILAYAH DI INDONESIA - Ria Oktorina; Andriyani Hapsari; Muhammad Zulkifli (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study analyzes the transformation of governance cooperation between government and business entities (PPP) in regional development in Indonesia, focusing on the evolution of regulations, dynamics of actors, and institutional capacity disparities between Central and regional. The study uses a qualitative-descriptive approach through content analysis of key regulatory documents, institutional reports, as well as meta-reviews of international literature, and integrates findings within the framework of good governance, networked governance, and evolutionary governance theory (EGT). The results showed that regulatory reform and an increase in the number of PPP projects have not been fully followed by strengthening regional capacity, policy harmonization, and accountability and transparency of implementation. The implementation of national PPP is still dominated by the central government with limited regional participation, regulatory fragmentation, and project concentration in the Java region, thus emphasizing the need for affirmative intervention for regions outside Java. The proposed policy implications include governance reforms, increased accountability, and affirmation strategies to accelerate equitable regional development in Indonesia.